THE EFFECT OF HURDLE RATE AND ORGANIZATIONAL INCENTIVE SYSTEMS ON COMMITMENT ESCALATION IN INVESTMENT DECISION MAKING - Sonata, Benaria; Nugroho, Paskah Ika (Among Makarti, 2022)
Escalation of commitment is a decision to increase or expand the commitment to a project or a particular investment even though the investment project or indicate failure. The purpose of the research is to examine whether the existence of hurdle rates and incentive system in the organization influence the manager's decision to do escalation of commitment. The study used a 2x2 between subjects experimental design with 76  participants from under graduate accounting majors who are currently taking management accounting course. The results of the research showed that: (i) hurdle rates affect the actions of managers doing the escalation of commitment; (ii) the incentive policy of the organization affects the escalation of commitment.; (iii) the interaction between hurdle rates and  incentive system of the organization doesn’t affect the escalation of commitment